2021
DOI: 10.1038/s41598-021-97450-w
|View full text |Cite
|
Sign up to set email alerts
|

A guide for the use of fNIRS in microcephaly associated to congenital Zika virus infection

Abstract: Congenital Zika Syndrome (CZS) is characterized by changes in cranial morphology associated with heterogeneous neurological manifestations and cognitive and behavioral impairments. In this syndrome, longitudinal neuroimaging could help clinicians to predict developmental trajectories of children and tailor treatment plans accordingly. However, regularly acquiring magnetic resonance imaging (MRI) has several shortcomings besides cost, particularly those associated with childrens' clinical presentation as sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Researchers studying children's development (Noreika et al, 2020 ; Turk et al, 2022 ) and spoken communication (Kelsen et al, 2022 ) have also signaled that longitudinal hyperscanning could advance their research. Moreover, others suggest that fNIRS would be a suitable technique to address the lack of longitudinal data pertaining to the development of cognition in infants and children (Miguel et al, 2019 ; Sato et al, 2021 ), neurodegenerative diseases (Bonilauri et al, 2020 ; Srinivasan et al, 2023 ), psychiatric disorders (Kumar et al, 2017 ; Ho et al, 2020 ), hearing after receiving a cochlear implant (McKay et al, 2015 ; Anderson C. A. et al, 2017 ; Zhou et al, 2022 ), and use of psychedelic substances (Scholkmann and Vollenweider, 2022 ). While these authors do not explicitly refer to hyperscanning as their technique of choice, INS recorded with fNIRS over multiple sessions could address several methodological aspirations (i.e., ecological validity, two-brain design, longitudinal assessment) at once.…”
Section: Ecologically Valid Measurements Of Social Interactionmentioning
confidence: 99%
“…Researchers studying children's development (Noreika et al, 2020 ; Turk et al, 2022 ) and spoken communication (Kelsen et al, 2022 ) have also signaled that longitudinal hyperscanning could advance their research. Moreover, others suggest that fNIRS would be a suitable technique to address the lack of longitudinal data pertaining to the development of cognition in infants and children (Miguel et al, 2019 ; Sato et al, 2021 ), neurodegenerative diseases (Bonilauri et al, 2020 ; Srinivasan et al, 2023 ), psychiatric disorders (Kumar et al, 2017 ; Ho et al, 2020 ), hearing after receiving a cochlear implant (McKay et al, 2015 ; Anderson C. A. et al, 2017 ; Zhou et al, 2022 ), and use of psychedelic substances (Scholkmann and Vollenweider, 2022 ). While these authors do not explicitly refer to hyperscanning as their technique of choice, INS recorded with fNIRS over multiple sessions could address several methodological aspirations (i.e., ecological validity, two-brain design, longitudinal assessment) at once.…”
Section: Ecologically Valid Measurements Of Social Interactionmentioning
confidence: 99%
“…Researchers studying children's development (Noreika et al, 2020;Turk et al, 2022) and spoken communication (Kelsen et al, 2022) have also signaled that longitudinal hyperscanning could advance their research. Moreover, others suggest that fNIRS would be a suitable technique to address the lack of longitudinal data pertaining to the development of cognition in infants and children (Miguel et al, 2019;Sato et al, 2021), neurodegenerative diseases (Bonilauri et al, 2020;Srinivasan et al, 2023), psychiatric disorders (Kumar et al, 2017;Ho et al, 2020), hearing after receiving a cochlear implant (McKay et al, 2015;Anderson C. A. et al, 2017;Zhou et al, 2022), and use of psychedelic substances (Scholkmann and Vollenweider, 2022). While these authors do not explicitly refer to hyperscanning as their technique of choice, INS recorded with fNIRS over multiple sessions could address several methodological aspirations (i.e., ecological validity, two-brain design, longitudinal assessment) at once.…”
Section: Longitudinal Perspectives On Interpersonal Neural Synchronymentioning
confidence: 99%
“…Preliminary studies have shown that the use of naturalistic stimuli (e.g., movies) enhances the reproducibility of functional connectivity and large-scale functional network findings [ 9 , 10 , 11 ]. In this scenario, recent modeling methods and complexity-based analysis have been suggested to address the limitations of the classical GLM-based analysis for non-structured paradigms [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%